Matching tumor risk with aggressiveness of treatment in men with multiple comorbidities and early‐stage prostate cancer. Issue 19 (16th July 2013) - Daskivich, Timothy J.; Chamie, Karim; Kwan, Lorna; Dash, Atreya; Greenfield, Sheldon; Litwin, Mark S.
Abstract : BACKGROUND: Men with multiple comorbidities are often overtreated for low‐risk prostate cancer, but it is unclear whether they are undertreated for high‐risk cancer, which has appreciable short‐term prostate cancer‐specific mortality. This study characterized the impact of comorbidity on treatment and survival in men with differing tumor risks. METHODS: The researchers sampled 1482 men with nonmetastatic prostate cancer at 2 Veterans Affairs hospitals between 1998 and 2004, using multivariate probit regression to determine probabilities of aggressive treatment among men with differing Charlson comorbidity scores within D'Amico tumor risk strata. Using competing‐risks regression, a comparison was made of 8‐year cancer‐specific mortality for men treated aggressively and nonaggressively among Charlson score‐tumor risk pairs. RESULTS: The study sample comprised 516 men (36%) with low‐risk, 475 men (33%) with intermediate‐risk, and 432 men (30%) with high‐risk prostate cancer. Men with high‐risk disease tended to have lower probability of aggressive treatment than other risk strata, regardless of comorbidity. Among men with Charlson scores 3+, probabilities of aggressive treatment did not increase with higher tumor risk (0.48, 0.61, 0.49 for low‐, intermediate‐, and high‐risk disease, respectively). In competing‐risks analysis, aggressive treatment was not associated with cancer‐specific survival benefit in men with multiple comorbidities (Charlson scores of 2 or 3+) and low‐ and intermediate‐risk disease, but there was a strong trend toward survival advantage in such men with high‐risk disease. CONCLUSIONS: Aggressiveness of treatment is poorly matched with tumor risk in men with significant comorbidity. Men with major comorbidities should consider conservative management for low‐ and intermediate‐risk disease and aggressive treatment for high‐risk disease. Cancer 2013;119:3446–3453. . © 2013 American Cancer Society . Abstract : Men with multiple comorbidities tended to have lower probability of aggressive treatment for high‐risk disease than other tumor risk strata, despite a strong trend toward survival advantage with aggressive treatment of high‐risk disease (but not low‐ or intermediate‐risk disease). Men with major comorbidities should consider conservative management for low‐ and intermediate‐risk disease and aggressive treatment for high‐risk disease.